DOES CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE INCREASE THE STOCK PRICE CRASH RISK? EVIDENCE FROM INDONESIA - Soeprajitno, Raden Roro Widya Ningtyas; Setiawan, Zephyra Violetta; Na’im, Ainun (Jurnal Akuntansi dan Keuangan Indonesia, 2023)
Indonesia fully supports efforts to disclose corporate social responsibility (CSR) to increase awareness of issues regarding the environment globally, as stated in the Sustainable Development Goals (SDGs). The connection between the disclosure of corporate social responsibility and the stock price crash risk is examined in this study. Furthermore, we analyse and check robustness and endogeneity issues to avoid variable bias selections. The study uses as its sample companies that are listed on the Indonesia Stock Exchange and follow the Global Reporting Initiative (GRI) for corporate social responsibility. It is found that companies with corporate social responsibility disclosures have a positive relationship with the stock price crash risk. Empirically, this finding contributes to broadening the scope of CSR research, while the relationship described in CSR is in line with the stock prices crash risk. This study shows that corporate social responsibility reporting has another side, which can be explained by management tactics. Thus, this study provides a new, broader, picture related to the characteristics of corporate events in Indonesia, showing that CSR disclosure patterns can result from corporate management interventions.